Influence of particle shape in additive manufacturing: Discrete element simulations of polyamide 11 and polyamide 12 - Schiochet Nasato, Daniel; Pöschel, Thorsten (Additive Manufacturing, 2020)
Understanding the mechanical behavior of powders used in additive manufacturing is a fundamental aspect to improve the quality and reliability of final parts. In this context, the role of particle shape for the powder bed quality is still not completely understood and sometimes overlooked. In this study, we propose a novel method to generate multisphere or clump representation from bi- or tridimensional templates of arbitrarily shaped particles. Particles from powders typically used in additive manufacturing, polyamide 11 (PA11) and polyamide 12 (PA12) are scanned (X-ray tomography) and used as prototypes for multisphere representation. Additionally, templates of modified PA11 particles (rounded through precipitation process) and SEM images of PA12 particles were used in multisphere reconstruction and further investigated. The multisphere representations retains not only most of the original template volume but also form factors associated with flowability characteristics – aspect ratio, flatness ratio, and elongation ratio. Using multisphere representations of the aforementioned powders, realistic discrete element method (DEM) simulations of the recoating step in additive manufacturing process are performed. The speed of the recoating mechanism follows realistic process velocities (100–250 mm/s). Packing density and roughness of powder beds are measured as a function of the recoating speed for different samples. Our results show that low aspect ratio (elongated) particles tend to form more compact layers of powders at lower recoating velocities. For higher recoating velocities, spherical particles perform better than elongated particles, due to better flowability characteristics. There is a clear dependency of recoating velocity and ideal particle shape for the deposition process, in contrast with the common assumption that spherical particles always perform better and should always be preferred.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Discrete Element Method (DEM); Multisphere approach; Particle shape; Recoating